PENILAIAN KINERJA OBJEK WISATA TAMAN MARGASATWA MANGKANG BERDASARKAN PERSEPSI PENGUNJUNG - Siti Handayani; Sariffuddin Sariffuddin (Diponegoro University, 2016)
Mangkang Zoo is one of main tourism object in Semarang developed with the primary functions of conservation and education through animal breeding attractions, and recreation as a supporting function. There are some problems of Mangkang Zoo on the development, management, and implementation that affect its performance and makes fluctuations number of visitors every year. This research aims to assess the performance of Mangkang Zoo tourism object according to the visitor's perception. The analytical method used in this study is a quantitative method and using accidental sampling with a sample of 100 respondents. Collecting data will be analyzed using descriptive statistical, IPA, Gap, and CSI. The performance assessment of Mangkang Zoo has good criteria with overall satisfaction value 0.66 or satisfied criteria, but the criteria are not exactly can be seen from the result of the performance assessment towards the variation and completeness of animals because most visitors are dissatisfied with the attractions of breeding animals that have poor performance. So most visitors prefer using visits to recreation because demand for the main attractions not be fulfilled.